A Whole-School Approach for the Promotion of Physical Activity: An Evaluation of Stakeholders’ and Educators’ Perceptions About Education in Six European Countries - Despoina Ourda; Lida Skoufa; Antonella Brighi; Diane Crone; Lowri Edwards; Alessandro Failo; Sophia Fourlari; Mikko Huhtiniemi; Timo Jaakkola; George Raptis; Paul Sellars; Elena Papacosta; et al. (Education Sciences)
Research has shown that a whole-school approach (WSA) is needed to increase student physical activity. There is a lack of empirical data on teachers’ opinions and needs regarding the implementation of a WSA approach to encourage physical activity. Our study aims to address this gap by identifying teachers’ and academics’ beliefs about the usefulness, content, and delivery mode of a WSA in fostering physical activity. To address the research aim, an exploratory mixed methods design was employed. Initially, a qualitative study with academics and stakeholders was conducted, followed by a quantitative investigation with teachers and school employees. In the first study, seven participants working in education took part in one-to-one interviews concerning their views on the usefulness, content, and delivery of whole-school education. The participants stressed the importance of the WSA and urged that educational authorities should consider the needs of children and the school community, promote teacher collaboration, pursue longevity, and engage with stakeholders and institutions throughout the process. In the second study, 160 school teachers and staff answered a survey about the content and delivery mode of an educational material for the promotion of WSA to fostering physical activity. The analyses indicated that participants preferred a three to six hours course, a hybrid mode of delivery, inclusion of best practices, and knowledge on how to implement a WSA. The study’s findings reveal several implications and recommendations for educators creating comprehensive school-based physical activity programs.